2010
DOI: 10.2527/jas.2008-1404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding diets containing increasing content of corn distillers dried grains with solubles to grower-finisher pigs on growth performance, carcass composition, and pork fat quality1

Abstract: Crossbred pigs (n = 512) with an average initial BW of 22.1 +/- 0.54 kg were used to evaluate growth performance, carcass characteristics, and pork fat quality of grower-finisher pigs fed corn-soybean meal diets containing increasing content of distillers dried grains with solubles (DDGS). One of 4 dietary treatments was randomly assigned to each pen within sex. Dietary treatment and sex were the main factors in a 3-phase feeding program (BW = 22 to 53 kg, 53 to 85 kg, and 85 to 115 kg). Dietary treatments con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
120
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(172 citation statements)
references
References 35 publications
(67 reference statements)
43
120
5
3
Order By: Relevance
“…Feeding DDGS had no effect (P > 0.05) on growth performance compared with the control in finishing pigs. This observation agreed with the findings of Xu et al (2010), who concluded that feeding diets containing 300 g DDGS/kg to growerfinisher pigs had no effect on growth performance. Similar to our results, DeDecker et al (2005) and Widmer et al (2007) reported that the inclusion of DDGS in diets fed to growingfinishing pigs had no effect on growth performance.…”
Section: Growth Performancesupporting
confidence: 92%
See 4 more Smart Citations
“…Feeding DDGS had no effect (P > 0.05) on growth performance compared with the control in finishing pigs. This observation agreed with the findings of Xu et al (2010), who concluded that feeding diets containing 300 g DDGS/kg to growerfinisher pigs had no effect on growth performance. Similar to our results, DeDecker et al (2005) and Widmer et al (2007) reported that the inclusion of DDGS in diets fed to growingfinishing pigs had no effect on growth performance.…”
Section: Growth Performancesupporting
confidence: 92%
“…In the present study, the pigs fed the diets containing DDGS increased the percentage of C18:2 and PUFA, but the C16:0 and SFA decreased in both the backfat and belly fat. Similarly, Dahlen et al (2011), Benz et al (2010 and Xu et al (2010) observed changes in the fatty acid profiles of pigs fed increased dietary DDGS, Total PUFA = ((C18:2) + (C18:3) + (C18:3) + (C20:2) + (C20:4)). Means within a row with different superscripts differ (P < 0.05).…”
Section: Carcass Fat Qualitymentioning
confidence: 79%
See 3 more Smart Citations